Honokiol as an α-glucosidase inhibitor - Zhu, Hua; Zhong, Xin (Frontiers in Pharmacology, 2024)
Honokiol, a naturally occurring compound from Magnolia obovata Thunb., has many biological activities, but its anti-α-glucosidase activity was still unclear. Therefore, we determined its inhibition effects against α-glucosidase. Activity assay showed that honokiol was a reversible mixed-type inhibitor on α-glucosidase, and its IC 50 value was 317.11 ± 12.86 μM. Fluorescence results indicated the binding of honokiol to α-glucosidase caused the reduction of α-glucosidase activity. 3D fluorescence and CD spectra results indicated the binding of honokiol to α-glucosidase caused the conformational change of α-glucosidase. Docking simulated the detailed interactions between honokiol and α-glucosidase, including hydrogen and hydrophobic bonds. All findings gave that honokiol could be used as natural inhibitor to develop α-glucosidase agents.